Do Stakeholder Orientation and Environmental Proactivity Impact Firm Profitability? - Brulhart, Franck (Journal of business ethics, 2019)
The impact of socially responsible corporate behavior on economic performance is a major preoccupation of managers today. This article explores the links between narrowly defined constructs: stakeholder orientation, environmental proactivity and profitability, from the perspectives of stakeholder theory and resource-based theory. We collected data on the food and beverage, and household and personal products industries. Using structural equation modeling, this paper makes two contributions. We found a negative link between companies simply having a higher stakeholder orientation and profitability. Importantly, however, environmental proactivity not only had a positive impact on profitability, but also appeared to mediate the relationship between stakeholder orientation and profitability. In other words, if a company is more environmentally proactive, it will be more attentive to a broad array of stakeholders, and this will in turn contribute positively to profitability.